Using an Expert Panel to Develop Social Support Program Sequencing for Young Adults With Type 1 Diabetes. Issue 6 (November 2017) - Brady, Patrick J.; Song, Hee-Jung; Butler, James
Background. Young adults living with type 1 diabetes (T1DM) often encounter poor health outcomes, such as uncontrolled blood glucose levels. Social support programs can be a helpful method to support T1DM self-management. Effectively planning and tailoring social support programs for young adults living with T1DM are crucial for improving these programs and associated outcomes. Objectives. This study convened an expert panel primarily composed of young adults living with T1DM to generate ideas and key components for sequential inclusion in social support programs prioritizing them. Method. Exploratory expert panel meetings consisting of four individuals living with T1DM were held where Nominal Group Technique and Ideawriting exercises were used to develop themes and discussion points. Results. Six themes emerged from the meetings representing areas of difficulty for young adults living with T1DM. Topics such as following self-care recommendations, nutrition, handling stress, coping with social situations, and navigating the health care system were identified as important issues facing young adults. Conclusions. By incorporating this approach into new or existing support group improved program discussions for young adults can be achieved and pertinent issues addressed, thus leading to improved health care outcomes.